KONTRIBUSI MR. ALEXANDER ANDRIES MARAMIS BAGI NEGARA KESATUAN REPUBLIK INDONESIA - Nency Aprilia Heydemans; Fienny Maria Langi (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2020)
Abstract The Unitary State of the Republic of Indonesia (NKRI) has distinctive cross-ethnic, religious and cultural characteristics that govern sovereignty of people's lives. The founders of the Unitary Republic of Indonesia represented the whole of the Indonesian people governing common life based on Pancasila as the philosophical and ideological basis of the Unitary Republic of Indonesia. Indonesia is a large country that has a history and historical figures. One historical figure is Mr. Alexander Andries Maramis (Mr. A. A. Maramis) who contributed to the independence of Indonesia and helped to form the basis of the State. The purpose of this study is (1) to know the life history and contribution of Mr. A. A. Maramis for the Republic of Indonesia. (2) Changes that occur after the contribution of Mr. A. A. Maramis for the Republic of Indonesia. This research uses the historical method with a descriptive approach through data analysis techniques, interviews, documentation and literature study. This paper is about to reveal that Mr. A. A. Maramis has an identity as a native of Minahasa (North Sulawesi) fighting for the independence of the Indonesian Nation both nationally and internationally. This is seen in nationalist identities and attitudes as markers of his struggle and for later generations. This article concludes that the next generation needs to build a collective memory of Mr. A. A. Maramis as a national hero who contributes to the value of humanity and nationalism. Keywords : A. A. Maramis, contribution, NKRI, nationalism, identity.